2011
DOI: 10.1258/ar.2011.100436
|View full text |Cite
|
Sign up to set email alerts
|

Normal values for renal parenchymal volume and kidney length as measured by non-enhanced multidetector spiral computed tomography

Abstract: The present animal study results showed that non-enhanced multidetector CT findings accurately reflect the RPV. The subsequent study performed in humans showed that the RPV of the presently sampled Chinese population was lower than the commonly quoted reference values obtained from Western populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It has been shown that kidney size is influenced by complex factors, including body mass index (BMI), height, gender, age, position of the kidneys, stenoses and number of renal arteries . Renal dimensions, such as parenchymal volume, an important index for clinical decisions, can be also assessed by non‐enhanced multidetector computed tomography (CT) . Cortical volume magnetic resonance imaging (MRI) measurements have also been reported, and the cortical volume can be calculated from voxel counting, a technique where areas of high‐signal renal cortex are extracted from the rest of the kidney .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that kidney size is influenced by complex factors, including body mass index (BMI), height, gender, age, position of the kidneys, stenoses and number of renal arteries . Renal dimensions, such as parenchymal volume, an important index for clinical decisions, can be also assessed by non‐enhanced multidetector computed tomography (CT) . Cortical volume magnetic resonance imaging (MRI) measurements have also been reported, and the cortical volume can be calculated from voxel counting, a technique where areas of high‐signal renal cortex are extracted from the rest of the kidney .…”
Section: Introductionmentioning
confidence: 99%
“…8 Renal dimensions, such as parenchymal volume, an important index for clinical decisions, can be also assessed by non-enhanced multidetector computed tomography (CT). 9 Cortical volume magnetic resonance imaging (MRI) measurements have also been reported, and the cortical volume can be calculated from voxel counting, a technique where areas of high-signal renal cortex are extracted from the rest of the kidney. 10 Sonographically, the most exact measurement of renal size is renal volume, but clinically, measurement of renal length is most practical and can be done in prone or supine position.…”
Section: Introductionmentioning
confidence: 99%